Answer: (f-g)(2)=14
Step-by-step explanation:
(f – g) (-2) means the same as subtracting f(2) and g(2). Since we are given f(x) and g(x), we can use them to solve. There are two ways to solve. One is to find f(2) and g(2), and then subtract them. Another way is to do (f-g)(x), then plug in x=2. I will show both methods.
Method 1
f(2)=3(2)²+1 [exponent]
f(2)=3(4)+1 [multiply]
f(2)=12+1 [add]
f(2)=13
g(2)=1-(2) [subtract]
g(2)=-1
(f-g)(2)=13-(-1) [subtract f(2) and g(2)]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Method 2
(f-g)(x)=3x²+1-(1-x) [distribute -1]
(f-g)(x)=3x²+1-1+x [combine like terms]
(f-g)(x)=3x²+x
(f-g)(2)=3(2)²+2 [plug in x=2, exponent]
(f-g)(2)=3(4)+2 [multiply]
(f-g)(2)=12+2 [add]
(f-g)(2)=14
--------------------------------------------------------------------------------------------------------
Now, we know that (f-g)(2)=14. We confirmed this with both methods.
Answer: 0.6 pounds
Step-by-step explanation: 3 divided by 5 = 0.6 pounds
Answer:
-64
Please Mark Brainliest If This Helped!
The relation is a function
It would be c because I used a graphing calculator lols